TRAINING ON MAKING BANANA NUGGETS IN KATELA VILLAGE, TERNATE ISLAND CITY, TERNATE CITY - Sherly Asriany; Sri Lestari (Ann Publisher, 2026)
Background. Kastela Village plays a significant role in the economic development of the city of Ternate, benefiting its residents. The development of local economic potential and the effective use of natural resources can at least contribute to the economic growth of the people. In general, the socio-economic condition of the people in Katela Village is still classified as belonging to the middle and lower economic groups. This is evident in the large number of impoverished families. This condition results in people becoming economically unproductive or less productive. Meanwhile, banana plants are pretty abundant in Kastela Village and are typically eaten raw or fried. Bananas that initially lacked economic value can be processed into products that are useful, economically valuable, and quite promising. Aims. Therefore, through the Community Service Program (PKM), the team aims to innovate a process for processing bananas with higher economic value. Method. The approach method is carried out by identifying problems, then approaching regional leaders (village heads and RW chairs) and local community leaders to obtain permission to conduct activities. Furthermore, form committees or working groups to prepare work plans and disseminate information in the community. Conclusion. Training activities for making banana nuggets have been carried out. Implications. The result of this activity is to be able to apply the expertise of making banana nugge